IN SILICO STUDY OF 12 PHYTOSTEROL COMPOUNDS IN MORINGA (MORINGA OLEIFERA LAMK.) SEED OIL ON 5Α-REDUCTASE ENZYME INHIBITION ACTIVITY AS ANTI-ALOPECIA - KORASSA, YULIUS BAKI; SAPTARINI, NYI MEKAR; MUSTARICHIE, RESMI; HENDRIANI, RINI; TJITDA, PUTRA JIWAMURWA PAMA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to determine the interaction of 12 phytosterol compounds in moringa seed oil to the 5α-reductase enzyme (PDB code: 7BW1) as anti-alopecia by in silico. Methods: The research was conducted using a molecular docking approach using autodock Tools 1.5.6. Data analysis was carried out by looked at the binding affinity values ​​and inhibition constants (Ki) of 12 phytosterol compounds, as well as visualization of amino acid interactions using Biovia Discovery Studio 2021. Results: 12 Phytosterol compounds had the potential to be a candidate for anti-alopecia medicines based on in silico test simulations using auto dock with high binding affinity values ​​in the range of-11.47 to-12.76 kcal/mol and stable inhibition constants in the range of 1.87. nM–4.30 nM involving hydrogen bonds with Arg179, Tyr178, Arg105, Arg114, Ser177, Tyr98, Glu57, and Tyr91 amino acids. Conclusion: Ergostadienol compound in moringa seed oil was predicted to be a better anti-alopecia on the inhibition of 5α-reductase enzyme with binding energy value was-11.60 kcal/mol, inhibition constant was 3.17 nM and interaction of amino acid residues on the inhibition of 5α-reductase enzyme was similar with native finasteride ligands namely Glu57 and Tyr91.